Seafloor spreading event in western Gulf of Aden during the November 2010–March 2011 period captured by regional seismic networks: evidence for diking events and interactions with a nascent transform zone. Issue 2 (22nd February 2016) - Ahmed, Abdulhakim; Doubre, Cécile; Leroy, Sylvie; Kassim, Mohamed; Keir, Derek; Abayazid, Ahmadine; Julie, Perrot; Laurence, Audin; Vergne, Jérome; Alexandre, Nercessian; Jacques, Eric; Khanbari, Khaled; et al.
Abstract: In November 2010, intense seismic activity including 29 events with a magnitude above 5.0, started in the western part of the Gulf of Aden, where the structure of the oceanic spreading ridge is characterized by a series of N115°-trending slow-spreading segments set within an EW-trending rift. Using signals recorded by permanent and temporary networks in Djibouti and Yemen, we located 1122 earthquakes, with a magnitude ranging from 2.1 to 5.6 from 2010 November 1 to 2011 March 31. By looking in detail at the space–time distribution of the overall seismicity, and both the frequency and the moment tensor of large earthquakes, we re-examine the chronology of this episode. In addition, we also interpret the origin of the activity using high-resolution bathymetric data, as well as from observations of seafloor cable damage caused by high temperatures and lava flows. The analysis allows us to identify distinct active areas. First, we interpret that this episode is mainly related to a diking event along a specific ridge segment, located at E044°. In light of previous diking episodes in nearby subaerial rift segments, for which field constraints and both seismic and geodetic data exist, we interpret the space–time evolution of the seismicity of the first few days. Migration of earthquakes suggests initial magma ascent below the segment centre. This is followed by a southeastward dike propagation below the rift immediately followed by a northwestward dike propagation below the rift ending below the northern ridge wall. The cumulative seismic moment associated with this sequence reaches 9.1 × 10 17 Nm, and taking into account a very low seismic versus geodetic moment, we estimate a horizontal opening of ∼0.58–2.9 m. The seismic activity that followed occurred through several bursts of earthquakes aligned along the segment axis, which are interpreted as short dike intrusions implying fast replenishment of the crustal magma reservoir feeding the dikes. Over the whole period, the opening is estimated to be ∼1.76–8.8 m across the segment. A striking feature of this episode is that the seismicity remained confined within one individual segment, whereas the adjacent en-echelon segments were totally quiescent, suggesting that the magma supply system of one segment is disconnected from those of the neighbouring segments. Second, we identify activity induced by the first intrusion with epicentres aligned along an N035°E-trending, ∼30 km long at the northwestern end of the active opening segment. This group encompasses more than seven earthquakes with magnitude larger than 5.0, and with strike-slip focal mechanisms consistent with the faults identified in the bathymetry and the structural pattern of the area. We propose that a transform fault is currently in formation which indicates an early stage of the ridge segmentation, at the locus of the trend change of the spreading ridge, which also corresponds to the boundary between a clear oceanic lithosphere and the zone of transform between continental and oceanic crust.